2018
DOI: 10.1186/s12879-018-3563-1
|View full text |Cite
|
Sign up to set email alerts
|

Diversity of Salmonella serotypes from humans, food, domestic animals and wildlife in New South Wales, Australia

Abstract: BackgroundSalmonella is an important human pathogen in Australia and annual case rates continue to increase. In addition to foodborne exposures, cases have been associated with animal and contaminated environment contact. However, routine surveillance in Australia has tended to focus on humans and food, with no reported attempts to collate and compare Salmonella data from a wider range of potential sources of exposure.MethodsSalmonella data from humans, food, animals and environments were collated from a range… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
39
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(45 citation statements)
references
References 47 publications
6
39
0
Order By: Relevance
“…S. Typhimurium was less frequent in chicken and egg products, but the predominant serovar in other foods, i.e., duck, pork and pork products, and other poultry where the serovar accounted for 43.9%, 35.2%, and 21.0% of the isolates, respectively. These findings are in agreement with other studies which reported S. Typhimurium as the principal serovar detected in dairy, pork, beef and mutton [16,19]. Detection of S. Typhimurium in chicken meat was low (9.4%) however relatively more frequent in fresh than frozen chicken meat.…”
Section: Discussionsupporting
confidence: 93%
“…S. Typhimurium was less frequent in chicken and egg products, but the predominant serovar in other foods, i.e., duck, pork and pork products, and other poultry where the serovar accounted for 43.9%, 35.2%, and 21.0% of the isolates, respectively. These findings are in agreement with other studies which reported S. Typhimurium as the principal serovar detected in dairy, pork, beef and mutton [16,19]. Detection of S. Typhimurium in chicken meat was low (9.4%) however relatively more frequent in fresh than frozen chicken meat.…”
Section: Discussionsupporting
confidence: 93%
“…Different studies have recorded that serovars found more frequently in dog faeces are similar to those found in humans [10,12,22,32,36,37]. In the present study, three serotypes were isolated, monophasic Salmonella Typhimurium (16.7%), S. Havana (50%) and S. Mikawasima (33.3%), which have also been implicated in human salmonellosis [38][39][40].…”
Section: Discussionsupporting
confidence: 58%
“…Different studies have recorded that serovars found more frequently in dog faeces are similar to those found in humans [ 10 , 12 , 22 , 32 , 36 , 37 ]. In the present study, three serotypes were isolated, monophasic Salmonella Typhimurium (16.7%), S .…”
Section: Discussionmentioning
confidence: 99%
“…Salmonella is a food-borne disease-causing zoonotic pathogen ( 1 ), and its occurrence has frequently been reported in recent years ( 2 , 3 ). More than 2,600 Salmonella serotypes have been identified and recorded ( 4 ).…”
Section: Introductionmentioning
confidence: 99%